Surface morphology transformation and densification behaviour of conventionally sintered AlFeCoNiSi high entropy alloys - Dewangan, Sheetal Kumar; Nagarjuna, Cheenepalli; Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Powder Metallurgy, 2023)
A preliminary study has been performed to understand the effect of pressureless sintering on the surface morphology of the AlFeCoNi alloy by the addition of the Si element. This study aims to determine the possibility of achieving the densification of high entropy alloy using the conventional sintering technique. The results indicate that the HEAs have a single-phase BCC structure even with the addition of Si. The thermodynamic simulation (CALPHAD) was used to predict the phase formation. The variation of crystallite sizes and lattice strains caused by sintering temperatures was also discussed. In addition, densification mechanisms occurring with the different sintering temperatures have been discussed. The formation of porosity was observed, however, the density of HEAs improved with increasing sintering temperature. Ultimately, it was suggested that the present HEAs required higher sintering temperatures and a longer time to achieve high density.
Keywords: Calphad; Conventional sintering techniques; Densification behaviour; Densifications; High entropy alloys; Morphology transformations; Pressureless-sintering; Single phasis; Sintering temperatures; Transformation behavior; CALPHAD; High-entropy alloy; mechanical alloying; powder metallurgy; sintering